Reflections on Engendering a Sustainable Community Within the Academy - Tung, Rosalie L. (Academy of Management Review, 2005)
This article discusses views on engendering a sustainable community within the Academy of Management. Statistics are given on diversity within the Academy, which has over 15,000 members from over 90 countries throughout the world. The author feels that, in order for the Academy to foster the true spirit of diversity, it must first broaden its range of offerings and become more welcoming of differences. To build and foster a truly sustainable community, she claims, the members of the Academy must be fully aware of the need to accommodate the diverse aspirations of all interest groups in striving to meet goals. Differences between the Academy's members are listed, including religion, ethnicity, and occupation.